Impacts of Tidal Locking on Magnetospheric Energy Input to Exoplanet Atmospheres - Fatemeh Bagheri; Alex Glocer; Ramon E. Lopez (The Astrophysical Journal)
We investigate the effect of planetary corotation on energy dissipation within the magnetosphere–ionosphere system of exoplanets. Using magnetohydrodynamic simulations, we find that tidally locked exoplanets have a higher cross polar cap potential (CPCP) compared to fast-rotating planets with the same magnetic field strength, confirming previous studies. Our simulations show that for a given interplanetary magnetic field, an increase in corotation period leads to a higher CPCP. Notably, this difference in CPCP between tidally locked and rotating planets persists across a range of solar wind conditions, including extreme environments such as those experienced by hot Jupiters. Furthermore, we observe that variations in corotation have little impact on CPCP for Earth-sized planets. These results underscore the significance of both corotation dynamics and planetary size in understanding how exoplanets interact with their stellar environments.